Multiphase Complex Coacervate Droplets - Lu, Tiemei (J Am Chem Soc, 2020)
[Image: see text] Liquid–liquid phase separation plays an important role in cellular organization. Many subcellular condensed bodies are hierarchically organized into multiple coexisting domains or layers. However, our molecular understanding of the assembly and internal organization of these multicomponent droplets is still incomplete, and rules for the coexistence of condensed phases are lacking. Here, we show that the formation of hierarchically organized multiphase droplets with up to three coexisting layers is a generic phenomenon in mixtures of complex coacervates, which serve as models of charge-driven liquid–liquid phase separated systems. We present simple theoretical guidelines to explain both the hierarchical arrangement and the demixing transition in multiphase droplets using the interfacial tensions and critical salt concentration as inputs. Multiple coacervates can coexist if they differ sufficiently in macromolecular density, and we show that the associated differences in critical salt concentration can be used to predict multiphase droplet formation. We also show that the coexisting coacervates present distinct chemical environments that can concentrate guest molecules to different extents. Our findings suggest that condensate immiscibility may be a very general feature in biological systems, which could be exploited to design self-organized synthetic compartments to control biomolecular processes.